CO-INFECTION OF AVIAN INFLUENZA H5N1 AND COCCIDIOSIS IN A 25-DAY-OLD BROILER: A CASE REPORT - Indira Laksmi Nandita; Tri Komala Sari; Ida Bagus Oka Winaya; Yeocelin Meida Utami; Ni Luh Putu Diah Septianingsih (Buletin Veteriner Udayana, 2025)
Avian Influenza (AI) is a highly pathogenic contagious disease in poultry caused by influenza A virus, particularly the H5N1 subtype. This disease significantly affects poultry health and causes considerable economic losses in poultry farming. This case report describes a 25-day-old broiler chicken from Demulih Village, Bangli, Bali, which showed symptoms of anorexia, weakness, greenish diarrhea, and rapid death. Epidemiological analysis revealed a morbidity rate of 33.3%, mortality rate of 22.7%, and case fatality rate of 68.3%. Anatomical pathology examination showed multiorgan hemorrhages, while histopathology revealed non-suppurative inflammation with lymphocytic infiltration in the brain, lungs, heart, pancreas, and intestine. Virus isolation using embryonated chicken eggs, along with hemagglutination (HA) and hemagglutination inhibition (HI) tests, confirmed Avian Influenza H5N1 infection. In addition, fecal examination identified Eimeria spp. oocysts, indicating coccidiosis. These findings highlight that H5N1 infection can be aggravated by parasitic co-infections, leading to increased mortality. Preventive measures should include routine vaccination, strict biosecurity, and good husbandry management to reduce the risk of disease spread in the future.